2023
DOI: 10.1186/s12913-023-09534-0
|View full text |Cite
|
Sign up to set email alerts
|

Implementing integrated care clinics for HIV-infection, diabetes and hypertension in Uganda (INTE-AFRICA): process evaluation of a cluster randomised controlled trial

Abstract: Background Sub-Saharan Africa is experiencing a dual burden of chronic human immunodeficiency virus and non-communicable diseases. A pragmatic parallel arm cluster randomised trial (INTE-AFRICA) scaled up ‘one-stop’ integrated care clinics for HIV-infection, diabetes and hypertension at selected facilities in Uganda. These clinics operated integrated health education and concurrent management of HIV, hypertension and diabetes. A process evaluation (PE) aimed to explore the experiences, attitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Twenty-eight articles in the review identified barriers to diagnosing NCDs (hypertension and diabetes). 14 , 15 , 20 , 35 61 The included studies reported barriers to and facilitators of diagnosing depression among PLWH. 42 , 50 , 62 73 Two studies reported both NCDs and depression.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-eight articles in the review identified barriers to diagnosing NCDs (hypertension and diabetes). 14 , 15 , 20 , 35 61 The included studies reported barriers to and facilitators of diagnosing depression among PLWH. 42 , 50 , 62 73 Two studies reported both NCDs and depression.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Eight studies from SSA, including Namibia, Uganda, Zimbabwe, Tanzania, and Malawi, reported NCD drugs, medication shortages, and supply chain difficulties. 35 , 41 , 43 , 48 , 51 , 53 55 For example, stock out of NCD medications, 43 , 51 , 53 , 54 including the nonavailability of HTN and DM medication at ART sites, 35 , 41 , 48 and challenges of NCD drug supply chains 44 , 47 , 54 , 55 were reported.…”
Section: Physical Opportunitymentioning
confidence: 99%
See 1 more Smart Citation